Time-delayed acoustic sink for extreme sub-wavelength focusing. (July 2020) - Ma, Fuyin; Chen, Jianyu; Wu, Jiu Hui
Highlights: An acoustic sink with perfect absorption at low frequencies is presented. Size of extreme sub-wavelength focus is much smaller than the sample size. The time-delayed focusing effect is demonstrated by experiment results. A universal time-delayed focusing mechanism is clearly revealed. Abstract: After a sound wave enters a Helmholtz resonator, it will be multiply reflected in the cavity and gradually overflow from the opening, just like water slowly flowing out from a water sink. In particular, if such a resonant cavity was arranged near the focus position in a time reversal focusing experiment, the cavity is equivalent to an acoustic sink, and an extreme sub-wavelength focus with a focal size much smaller than the sample size can be achieved. The physical mechanism of this sub-wavelength focusing is that after the sound wave reaches the focus, due to the fact that the arranged cavity has a perfect sound absorbing ability, a large part of the acoustic energy would enter the cavity and then be lost. However, in the loss stage, the localized high-intensity sound energy in the resonant cavity will continuously overflow to the opening. These sounds belong to evanescent wave, and can only be localized near the orifice, so that a very small focus with the size as aperture will be formed. Theoretically, the realization of this extreme sub-wavelength focus resolution depends on the modification of the evanescent wave field. This time-delayed sub-wavelength focusing effect was visually demonstrated by time reversal measurement results in time domain, and the extreme sub-wavelength feature was intuitively demonstrated by results in frequency domain.